1984
DOI: 10.1111/j.1399-3011.1984.tb02725.x
|View full text |Cite
|
Sign up to set email alerts
|

Syntheses and properties of tertiary peptide bond‐containing polypeptides.

Abstract: Oligo(Leu)s containing Pro or (Dmob) Leu residues were prepared by the stepwise elongation and fragment condensation methods. The peptides prepared were the following: Boc‐Leun‐OBzl (n = 3–6 and 9), Boc‐Pro‐Leu3‐OBzl, Boc‐Leun‐Pro‐OBzl (n = 3–5), Boc‐Leun‐Pro‐Leu3‐OBzl (n = 3 and 4), Boc‐(Leu4‐Pro)2‐OBzl, Boc‐Leu3‐Pro‐Leun‐Pro‐Leu3‐OBzl (n = 6 and 7), Boc‐Leu3‐Gly‐(Dmob) Leu‐OMe, Boc‐[Leu3‐Gly‐(Dmob) Leu‐Leu3]n‐OBzl (n = 1 and 2). The insertion of the Pro and Gly‐(Dmob) Leu residues into a peptide chain caused… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
6
0

Year Published

1984
1984
2016
2016

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 57 publications
(7 citation statements)
references
References 20 publications
1
6
0
Order By: Relevance
“…The peptides constructed of a-helical and coiled structures usually have high solubility in organic solvents due to having fewer intermolecular hydrogen bonded structures. The insolubility of peptides is largely caused by the formation of the 8-sheet structure through the intermolecular hydrogen bonding: a fully developed 0-sheet structure remarkably reduced solubility of peptides, as previously reported (12). In the same and other papers, we also reported that the insertion of a tertiary peptide bond into a central position of peptide chains ( Fig.…”
supporting
confidence: 86%
See 1 more Smart Citation
“…The peptides constructed of a-helical and coiled structures usually have high solubility in organic solvents due to having fewer intermolecular hydrogen bonded structures. The insolubility of peptides is largely caused by the formation of the 8-sheet structure through the intermolecular hydrogen bonding: a fully developed 0-sheet structure remarkably reduced solubility of peptides, as previously reported (12). In the same and other papers, we also reported that the insertion of a tertiary peptide bond into a central position of peptide chains ( Fig.…”
supporting
confidence: 86%
“…This is based on the consideration that the precise prediction of the /%sheet + a-helix transition is difficult for protected peptides having medium sizes (8, [15][16][17][18][19][20]. Solubility of protected peptides is also strongly dependent on the numbers and positions of such tertiary peptide bonds as X-Pro and X-(Z)Y bonds (12). Therefore, in addition to the randomness, the solubility prediction is also performed on the basis of the existence of the tertiary peptide bonds.…”
Section: Predictive Methodsmentioning
confidence: 99%
“…The greatest problem of peptide chemistry is peptide insolubility, of either unprotected peptides in aqueous buffer or fully protected peptides in organic solvents . This obstacle has prevented the development of many areas of peptide chemistry: for example, a general method for the assembly of protected peptide fragments.…”
Section: Introductionmentioning
confidence: 99%
“…2 ) It has been shown that the insertion of a large steric group (2,4-dimethoxybenzyl) reversibily attached to 1 out of 5 alanine nitrogens enhances the solubility of the protected penta-alanine largely, presumably by disturbance of its regularity and by lowering the probability for an effective aggregation (cf. [15][16][17].…”
Section: Discussionmentioning
confidence: 99%